The Influence of Self-Efficacy and Work Life Balance on Employee Performance through Organizational Commitment as a Mediating - Basuki, Aiyi Apresia; Suhermin, Suhermin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines and analyzes the result of self-efficacy and work life balance on the organization commitment at Bank Jatim, branch of Dr.Soetomo. The research applies quantitatively. Furthermore, the data collection technique used was saturation sampling, when samples were drawn from every member of the population, i,e, 45 employees of Bank Jatim, branch of Dr. Soetomo. The method of data analysis that was employed was the Partial Least Square (PLS) program with a software instrument of SmartPLS 3.0 version. The findings indicate that while work-life balance has a favorable but negligible impact on workers' performance, self-efficacy has a beneficial influence on employees' performance. Meanwhile, employee performance is positively and significantly impacted by organizational commitment. Moreover, both self-efficacy and work-life balance has a substantial and favorable impact on employees’ performance through organizational dedication. Similarly, work-life balance significantly and favorably affects employees’ performance through organizational dedication.